Evaluation of cell-free DNA from papanicolaou smears and peripheral blood to detect endometrial cancer - Wang, Yao; Yang, Jia-Xin; Yu, Mei (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to identify tumor-derived DNA in Papanicolaou (Pap) smears and plasma specimens from patients with endometrial cancer or endometrial intraepithelial neoplasia (EC/EIN).MethodsTumor tissue, peripheral blood, and Pap smear samples were collected from 84 patients with EC and EIN. Somatic mutations in tumor specimens were analyzed using targeted exome sequencing with a 363-cancer-related gene panel. Circulating single-molecule amplification and resequencing technology (cSMART) was used to evaluate somatic mutations in Pap smear and plasma circulating cell-free DNA (cfDNA).ResultsHigher pathological grades and lymph node metastases in EC were associated with elevated plasma cfDNA concentrations (p < 0.05 for both). Mutations corresponding to tissue samples were identified in 42.9% of plasma cfDNA and 77.4% of Pap smear cfDNA, with Pap smears demonstrating a higher detection rate (p < 0.05). In patients with EC, the detection rate of consistent mutations in cfDNA from peripheral blood was significantly elevated in those with higher pathological grades, lymphovascular space involvement, and lymph node metastasis (p < 0.05). The detection rate of consistent mutations in cfDNA from Pap smears was significantly higher in the EC group (p < 0.001).ConclusionMulti-gene panels can detect tumor-derived DNA in cfDNA from both blood and Pap smears of patients with EC, with Pap smear cfDNA potentially offering higher efficacy for liquid biopsies in EC. This approach could complement tissue biopsies for early diagnosis and risk stratification, warranting further investigation into the clinical utility of liquid biopsies for EC management.